2019
DOI: 10.1016/j.heliyon.2019.e01621
|View full text |Cite
|
Sign up to set email alerts
|

Alkyd resin from rubber seed oil/linseed oil blend: A comparative study of the physiochemical properties

Abstract: This study was aimed at the synthesis and characterization of alkyd from rubber seed/linseed oil blends. Different percentages of rubber seed oil were blended with linseed oil for the preparation of alkyd via condensation polymerisation of monoglyceride with phthalic anhydride. Physiochemical properties like colour, acid value, saponification value, iodine value, drying schedule, chemical resistance were evaluated for the different alkyd samples synthesized. The colour of the different samples was unaffected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…The specific gravity of the test alkyd resins was not considerably greater than the specific gravity of the control alkyd resins (47.40) and the viscosity of commercially manufactured alkyd resin (32.34 m2/s). These results were comparable to those found in Otabor's work [20], implying that the test alkyd resins will outperform commercially available varieties in industrial applications if well-controlled.…”
Section: Physico-chemical Properties Of the Theventia Peruviana Alkyd...supporting
confidence: 82%
“…The specific gravity of the test alkyd resins was not considerably greater than the specific gravity of the control alkyd resins (47.40) and the viscosity of commercially manufactured alkyd resin (32.34 m2/s). These results were comparable to those found in Otabor's work [20], implying that the test alkyd resins will outperform commercially available varieties in industrial applications if well-controlled.…”
Section: Physico-chemical Properties Of the Theventia Peruviana Alkyd...supporting
confidence: 82%
“…The high percentage yield of the Afzelia africana aril cap oil revealed by the results (Table 1) indicates its availability and sustainability for commercial use. The moderate value of iodine shows a reasonable amount of unsaturation that is readily available for sulphonation reaction [21]. The sulphonated oil synthesized was virtually free from inorganic salts.…”
Section: Physicochemical Propertiesmentioning
confidence: 97%
“…Lipid-based films have the highest resistance degree to moisture migration compared to protein and polysaccharide films, but they are difficult to apply due to their thickness and greasy surface. A group of authors has reported (Wang et al, 2019;Otabor et al, 2019) flaxseed oil to be used for composite films formation, which are based on chitosan and potato protein. In that way, the addition of flaxseed oil contributes to an excellent moisture barrier and elastic and durable films formation, due to the high percentage of polyunsaturated fatty acids in flaxseed oil, which absorb oxygen from the air.…”
Section: Biopolymers For Edible Oils Packagingmentioning
confidence: 99%